Sleep: A Novel Mechanistic Pathway, Biomarker, and Treatment Target in the Pathology of Alzheimer's Disease?. Issue 8 (August 2016) - Mander, Bryce A.; Winer, Joseph R.; Jagust, William J.; Walker, Matthew P.
Abstract : Sleep disruption appears to be a core component of Alzheimer's disease (AD) and its pathophysiology. Signature abnormalities of sleep emerge before clinical onset of AD. Moreover, insufficient sleep facilitates accumulation of amyloid-β (Aβ), potentially triggering earlier cognitive decline and conversion to AD. Building on such findings, this review has four goals: evaluating (i) associations and plausible mechanisms linking non-rapid-eye-movement (NREM) sleep disruption, Aβ, and AD; (ii) a role for NREM sleep disruption as a novel factor linking cortical Aβ to impaired hippocampus-dependent memory consolidation; (iii) the potential diagnostic utility of NREM sleep disruption as a new biomarker of AD; and (iv) the possibility of sleep as a new treatment target in aging, affording preventative and therapeutic benefits. Trends: A bidirectional, causal interaction exists between NREM sleep and Aβ pathophysiology that may contribute to Alzheimer's disease (AD) risk and progression. The disruption of NREM sleep may represent a novel pathway through which cortical Aβ impairs hippocampus-dependent memory consolidation. The disruption of NREM sleep physiology offers potential diagnostic utility in the form of a non-invasive biomarker of Aβ pathology, AD risk, and/or AD pathophysiological progression. Evidence implicates sleep disturbance as a consequence and cause of AD progression; one that is modifiable, offering preventative and therapeutic treatment potential.